Epidemiology of Guillain-BarréSyndrome in Iranian Children Aged 0-15 Years (2008-2013) - Tonekaboni, Seyed Hassan; Mahmoudi, Sussan; Abdollah Gorji, Fatemeh; Nejad Biglari, Habibe; Taghdiri, Mohammad Mahdi; Etemadi, Koroush; Ghofrani, Mohammad; Karimi, Abdollah; Rezaei Zadeh Rukerd, Mohammad (Iranian Journal of Child Neurology, 2021)
Abstract Objective: Guillain-Barre Syndrome (GBS) is an acute inflammatory polyneuropathy characterized by a rapid progressive symmetric weakness. This is the most common cause of Acute Flaccid Paralysis (AFP) in most parts of the world. This study was carried out to investigate the epidemiological features of GBS in Iranian children. Materials & Methods: Data were extracted using the AFP surveillance system: a National screening program to detect all cases of AFP aged 0-15 years, around the country. National Population Statistics data and AFP demographic data during 2008-2013 intervals was obtained from the relevant authorities in ministry of health. GBS cases were then extracted from this data base. Chi-square and Fisher's exact test were used for statistical analysis. Results: 1884 cases of GBS were identified in years of study and average annual incidence rate was 1.72 per 100,000 populations. The highest incidence rate was in the range of 0-5 years. There was no statistically significant relation between the incidence of GBS and the season in the whole country. Conclusion: High costs of GBS treatment, morbidity and occasional mortality and the number of new cases which is estimated to be about 300 people per year, need particular attention of health system.